2020
DOI: 10.1002/jmri.27325
|View full text |Cite
|
Sign up to set email alerts
|

MRI in Children With Pyriform Sinus Fistula

Abstract: Background A variety of imaging modalities have been described for the diagnosis of congenital pyriform sinus fistula (CPSF). To date, there have been few MRI reports. Purpose To evaluate MRI findings of CPSF and interobserver reliability. Study Type Retrospective. Population In all, 115 patients aged 23 days to 15.4 years at operation. Field Strength/Sequence 3.0T/axial T1‐weighted image (T1WI)‐SPIR, axial T2WI, axial T2WI‐STIR, coronal T2WI‐SPIR, diffusion‐weighted imaging (DWI), axial and coronal gadolinium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Only 15 cystic masses with air bubbles were diagnosed as CPSF by US clinically. The sign of air-bubbles in the cyst was identified as the characteristic indicator of CPSF in previous studies (18). Our results were comparable with those of the studies, reporting 15 air-bubble cysts diagnosed on US and 24 air-bubble cysts diagnosed on CT. Obviously, CT showed significantly higher detection rates of the air-bubble sign in lesions than US, which may be explained by the fact that the amount of air filled in the lesions was usually small and the individual bias of the US operators.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Only 15 cystic masses with air bubbles were diagnosed as CPSF by US clinically. The sign of air-bubbles in the cyst was identified as the characteristic indicator of CPSF in previous studies (18). Our results were comparable with those of the studies, reporting 15 air-bubble cysts diagnosed on US and 24 air-bubble cysts diagnosed on CT. Obviously, CT showed significantly higher detection rates of the air-bubble sign in lesions than US, which may be explained by the fact that the amount of air filled in the lesions was usually small and the individual bias of the US operators.…”
Section: Discussionsupporting
confidence: 90%
“…CPSF in the neonates showed other distinctive imaging findings on contrast-enhanced CT scan, especially having advantages in terms of confirming the exact location and extent of involvement of a lesion, which is helpful to diagnose the CPSF without specific air bubbles. Based on the anatomical location of the cervical fascial space ( 19 , 20 ), these lesions were located in the visceral space, as a characteristic imaging manifestation of the disease ( 18 ). With the higher spatial and density resolution than the US, CT is more sensitive in detecting the relationship between cysts with the retropharyngeal space, mediastinum, thyroid, and airway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The typical presentations of lesions in pyriform sinus fistula are recurrent low‐neck abscesses, acute suppurative thyroiditis, and neck masses 14–16 . Approximately, 90% of these sinus tracts are situated on the left side of the neck, which may be due to embryonic development 17–19 . An internal fistula is usually located at the tip or base of the pyriform fossa 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the application of computed tomography (CT) and magnetic resonance imaging (MRI) in imaging evaluation of chronic wounds (8)(9)(10)(11)(12); CT scan relay high anatomic detail of chronic wounds and assess surrounding bone destruction (3), and MRI has high resolution and sensitivity to soft tissue without ionizing radiation. It is possible to combine CT and MRI with sinography/fistulography, which allows for visualization of internal features of the sinus/fistula by instilling contrast agent into the external opening (9).…”
Section: Introductionmentioning
confidence: 99%